Competitive Strategy Analysis Of Manufacturing Companies (A Case Study On Pt Valeo Indonesia - Ac Batam) - Frans Natanael Simangunsong* (Riwayat: Educational Journal of History and Humanities, 2023)
PT Valeo AC Indonesia – Batam is a manufacturing company that produces car parts such as wipers. The production capacity owned by PT Valeo AC Batam is based on machines and workers' ability to produce more than one million wipers every month. However, PT Valeo's product sales have started declining since February 2022. PT Valeo AC Batam needs to increase this sales decline so that it can survive and develop by formulating the right competitive strategy to gain a competitive advantage. This study aims to determine the internal and external environmental conditions of PT Valeo AC Indonesia - Batam. In addition, it is necessary to formulate other suitable competition methods for companies doing business and dealing with competitors. The method used in this study is a mixed method of quantitative and qualitative analysis using a case study approach. Source of data is primary data collected through interviews and observation. At the same time, secondary data was obtained from company literature, books, magazines and internal records. Sampling in this study used a purposive sampling method of twelve sources, and the validity of the data used was based on the source triangulation method. The data analysis method used in this study is the IFE Matrix, EFE Matrix, IE Matrix, SWOT Matrix and QSPM Matrix based on the results of internal and external environmental analysis of PT Valeo AC Indonesia – Batam. The results showed that the IFE matrix score was 2.780 and the EFE matrix score was 3.266, so PT Valeo AC Indonesia - Batam's position in the IE matrix is in the cell II, which is a growth and build strategy. From the results of the SWOT matrix, the company has 7 alternative strategies, consisting of 6 market penetration strategies and 1 market development strategy. The strategy alternative which is the top priority based on the evaluation of the QSPM matrix is the market development strategy. The recommended strategy for PT Valeo AC Indonesia - Batam to face competition is to enter nearby markets such as ASEAN to be able to help the company expand its customer base, increase sales, and reduce dependence on existing markets.